The Relationship Between Perceptions and The Role of Midwives in the Use of P4K Stickers for Pregnant Women at Pekapuran Raya Community Health Center Working Area - Bella Chaidir; Susanti Suhartati; Yayuk Puji Lestari; Meldawati Meldawati (Healthy-Mu Journal, 2024)
The maternal mortality rate (MMR) in Indonesia in 2019 was 4627 people, this number has increased compared to 2019 which was 4,221 deaths. In 2022, (MMR) for South Kalimantan province will reach 136 people. This figure has decreased compared to the achievement in 2021 of 205 people, which means there will be a decrease in the achievement of the Maternal Mortality Rate in 2022. P4K is an activity facilitated by midwives to increase the active role of husbands, families, and communities in planning safe births using P4K stickers. The research objective was to identify the relationship between the use of P4K stickers among pregnant women in the Pekapuran Raya Community Health Center Work Area. This research aims to identify the relationship between the perception and role of midwives in the use of P4K stickers among pregnant women in the Pekapuran Raya Community Health Center Work Area. This research used quantitative and cross-sectional methods, with a sample size of 30 pregnant women. Results of the analysis show that there is a relationship between perception (ρ-value = 0.002) and the use of P4K stickers and there is a relationship between the role of midwives (ρ-value = 0.000) and the use of P4K stickers in the Pekapuran Raya Community Health Center Working Area. Based on the results of this research, it can be concluded that the perception of pregnant women and the role of midwives is good in implementing the use of P4K stickers.